2012
DOI: 10.1002/fam.2151
|View full text |Cite
|
Sign up to set email alerts
|

Fire performance and thermal stability of polypropylene nanocomposites containing organic phosphinate and ammonium polyphosphate additives

Abstract: SUMMARY In order to develop polymer‐clay nanocomposites with reduced flammability by incorporation of char‐forming conventional nitrogen and phosphorus based flame retardants at low loading levels, the polypropylene‐clay nanocomposites were prepared by melt blending method with Cloisite 15A (15A), organic phosphinate (OP) and ammonium polyphosphate (AP) additives. Thermal analysis shows that addition of 5% 15A along with 15% (w/w) OP in polypropylene (PP)/PPgMA increases the thermal stability of PP/PPgMA/OP/15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, it can be concluded that phosphorus-based flame retardants have quite satisfactorily reinforced PP against flame. [25], APP-20 [26], APP-20 [27], APP-20 [28], APP-20 [23], APP-25 [29], APP-25 [30], APP-25 [31], APP-25 [32], APP-25 [33], APP-25 [34], APP-25, m-APP-25 [35], APP-25, mc-APP-25 [36], m-APP-25 [37], APP-30 [38], APP-30 [39], APP-30 [40], mc-APP-30 [41], APP-30, mc-APP-30 [42], APP-30, mc-APP-30 [43], APP-30, mc-APP-30 [44], APP-30, mc-APP-5, mc-APP-10, mc-APP-15, mc-APP-20, mc-APP-25, mc-APP-30 [45], APP-35, m-APP-35 [46], APP-35, m-APP-35 [47], APP-40, mc-APP-40 [48], APP-25, P-CA-25 [49], APP-25 [50], APP-IFR-20 [51], P-IFR-10, P-IFR-15, P-IFR-20, P-IFR-25 [52], P-IFR-20 [53], P-IFR-28 [54], P-IFR-28 [55], PN-IFR-30 [56], P-FR-30 [57], P-FR-20 [58], , mc-BDP-10, mc-BDP-20 [59], OP-20 [60], AHP-24 [61], ALPi-30 [62], PEPA-40 [63].…”
Section: Phosphorus-based Flame Retardantsmentioning
confidence: 99%
“…Therefore, it can be concluded that phosphorus-based flame retardants have quite satisfactorily reinforced PP against flame. [25], APP-20 [26], APP-20 [27], APP-20 [28], APP-20 [23], APP-25 [29], APP-25 [30], APP-25 [31], APP-25 [32], APP-25 [33], APP-25 [34], APP-25, m-APP-25 [35], APP-25, mc-APP-25 [36], m-APP-25 [37], APP-30 [38], APP-30 [39], APP-30 [40], mc-APP-30 [41], APP-30, mc-APP-30 [42], APP-30, mc-APP-30 [43], APP-30, mc-APP-30 [44], APP-30, mc-APP-5, mc-APP-10, mc-APP-15, mc-APP-20, mc-APP-25, mc-APP-30 [45], APP-35, m-APP-35 [46], APP-35, m-APP-35 [47], APP-40, mc-APP-40 [48], APP-25, P-CA-25 [49], APP-25 [50], APP-IFR-20 [51], P-IFR-10, P-IFR-15, P-IFR-20, P-IFR-25 [52], P-IFR-20 [53], P-IFR-28 [54], P-IFR-28 [55], PN-IFR-30 [56], P-FR-30 [57], P-FR-20 [58], , mc-BDP-10, mc-BDP-20 [59], OP-20 [60], AHP-24 [61], ALPi-30 [62], PEPA-40 [63].…”
Section: Phosphorus-based Flame Retardantsmentioning
confidence: 99%
“…This PP/PP‐gAPP/Ch/KF shows a similar degradation temperature to the reference samples with 30 and 50 wt% of MH. This indicates that the combination of Ch with KF using PP‐gAPP as compatibilizer could have similar degradation behavior than reference samples with higher MH loadings 36–40 …”
Section: Resultsmentioning
confidence: 85%
“…On the other hand, the PP/PP‐gAPP sample shows a remarkable reduction in HRR and THR in which the PHRR was reduced by 25% compared to the neat PP with a significant increase in the t‐ign of 46 s. This corroborates the significant enchantment in flame retardancy provided by the APP. The reported FR mechanism of phosphated compounds is the dilution effect related to the formation of PO· radicals during combustion that could combine with active radicals such as H· and OH· from the burning polymer to terminate the combustion chain reaction, thus improving the thermal stability of the polymers by delaying their degradation 36,37 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 An IFR generates a barrier effect of an intumescent carbonaceous char created by the combined action of the compounds. 35,36 The char layer reduces heat transfer between the heat source and the material surface, and limits combustible gas transfer from the material toward the flame as well as the diffusion of oxygen into the material. In addition, the char layer may prevent dripping from the material.…”
Section: Introductionmentioning
confidence: 99%